PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL DAN MOTIVASI TERHADAP HASIL PRAKTIK IBADAH SISWA DI SMP - parman, parman; Fitrah, Yundi; Emosda, Emosda (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
Reasoning of this research is still the low of education value of Islam, the low of enthusiasm and willingness to learn religion, the low of awareness practices religious service, the low of ability in choosing study media applied. Media audiovisual can assist optimal of ability of each student, builds student enthusiasm in learning, has skillful character, self-supporting and sensitive. This research aim to (1) knows usage influence of media audiovisual and print media to result of practice of student religious service, (2) knows motivation to result of practice of student religious service, and (3) knows interaction of motivation to result of practice of student religious service applies media audiovisual. This research type is quasi esperimen with factorial design 2x2. In process of this experiment done observation at two group of study that is group of experiment given treatment with media audiovisual, and group of control with print media. This research subject is class student VII even semester which amounts to 48 mans, what consisted of class VII A 24 as control class and class VII B 24 as experiment class. Instrument applied in this research is instrument of motivation and instrument practice of religious service. instrument of Motivation is made in the form of scale enquette likert. instrument validity of Item practice of religious service and motivation enquette item of religious service applies technique formula product moment. To test hypothesis applied factorial of 2 x 2 Anova two lines and test Tukey. From result of inferential research that: (1) There is usage influence of media audiovisual to result of practice of student religious service. (2) there is no Pengaruh motivation to result of practice of student religious service. (3) there is no usage influence of media audiovisual to result of practice of student religious service having high motivation. (4) there is no usage influence of media audiovisual to result of practice of student religious service having low motivation. (5) there are no interaction between visual audio medias with motivation to practice of religious service in education teaching of Islam. Keyword: Study Media, Motivation, Skill Is having religious service